PEMBERDAYAAN LITERASI KEAGAMAAN DAN KARAKTER ISLAMI BAGI SISWA DI PULAU AY BANDA NEIRA - St. Jumaeda; Eko Wahyunato Prihono; Saddam Husein; Muhamad Tualepe; Putri Wulandari Saharudin (Universitas PGRI Yogyakarta, 2026)
The low level of students’ religious literacy and Islamic character development in archipelagic areas, particularly in Qur’an reading skills, the application of basic tajwid, Islamic art development, and habituation of religious activities, became the main background for this Community Service Program. This program aimed to improve students’ religious literacy and strengthen their Islamic character through Qur’an learning guidance, Islamic calligraphy training, and Yasin recitation activities in Pulau Ay Village, Banda Neira District, Central Maluku Regency. The participants consisted of students of State Elementary School 182 Maluku Tengah and State Junior High School 10 Maluku Tengah. The implementation method employed a Participatory Action Research (PAR) approach through preparation, implementation, and evaluation stages using participatory and educational approaches. The activities were conducted through group learning, direct practice, and mentoring sessions for students. Program evaluation used coaching evaluation sheets analyzed descriptively using quantitative methods. The results showed improvements in student participation, Qur’an reading ability, Islamic calligraphy skills, and discipline in Yasin recitation activities. This community service program contributed positively to strengthening students’ religious character in archipelagic areas. Keyword: religious literacy, Islamic character, Qur'an development, calligraphy art, Yasin program